(untitled) (Bangladesh Journal of Botany, 2008)
Floppy and compact discs gradually loose their quality. On closer examination deteriorated discs showed diverse microbial growth on their surfaces. Among the associated organisms 15 actinomycetes and 12 bacterial isolates were selected for detailed studies. The selected actinomycetes were Streptomyces diastaticus, S. rimosus, S. cyaneus, S. olivaceoviridis, S. halstedii, S. fulvissimus, S. albidoflavus, S. exfoliates and S. griseoflavus and the bacterial strains were Bacillus lentus, B. circulans, B. badius, B. laterosporus, B. larvae and B. thuringiensis. In addition, Micrococcus sedentarius was also isolated. Utilization of crushed disc materials was observed during this study, which was indicative of deterioration of floppy and compact discs. Â Key words: Compact disc, Floppy disc, Microorganisms, Recalcitrant doi:10.3329/bjb.v37i1.1557 Bangladesh J. Bot. 37(1): 7-14, 2008 (June)